2018
DOI: 10.1021/acsami.8b14457
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel β-Bis(N,N-diarylamino)-Substituted Porphyrin for Dye-Sensitized Solar Cells under 1 sun and Dim Light Conditions

Abstract: In this work, we have synthesized a novel porphyrin dye named SK7, which contains two N,N-diarylamino moieties at two β-positions as electron-donating units and one carboxy phenylethynyl moiety at the meso-position as an electron-withdrawing, anchoring group. This novel dye was tested for the application in dye-sensitized solar cells. The light-harvesting behavior of SK7 and YD2 was investigated using UV–vis absorption and density functional calculation. The electron transport properties at the TiO2/dye/electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…The SK7-based DSSC exhibited PCE of 19.72% and 15.54% under the illumination of T5 fluorescent and LED lamps, respectively. In contrast, the YD2-dye-based DSSC showed PCE of 20.00% and 16.57% under the illumination of the T5 fluorescent and LED lamps, respectively [ 92 ]. Liu et al demonstrated the influence of a compact blocking layer on the performance of a Y123-dye-based solar cell for indoor applications [ 93 ].…”
Section: Pv Cells For Indoor Applicationsmentioning
confidence: 99%
“…The SK7-based DSSC exhibited PCE of 19.72% and 15.54% under the illumination of T5 fluorescent and LED lamps, respectively. In contrast, the YD2-dye-based DSSC showed PCE of 20.00% and 16.57% under the illumination of the T5 fluorescent and LED lamps, respectively [ 92 ]. Liu et al demonstrated the influence of a compact blocking layer on the performance of a Y123-dye-based solar cell for indoor applications [ 93 ].…”
Section: Pv Cells For Indoor Applicationsmentioning
confidence: 99%
“…DSCs also possess many unique advantages over other emerging PV technologies, including less dependence on incident light angle, 12–15 a tailor‐made spectral response, 16–18 and unique charge separation characteristics, 19,20 making them suitable for power generation for indoor electronic appliances. In the limited papers reporting the superiority of DSCs under dim light use, 1,21–27 two important facts can be found. The first one is that the test condition (artificial light) is not clearly defined or standardized, so the comparison among the results from different research groups is practically difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is that the test condition (artificial light) is not clearly defined or standardized, so the comparison among the results from different research groups is practically difficult. The second one is that the papers reporting high PCEs under artificial lights are achieved almost without exception by introducing new materials such as novel sensitizers or novel redox couples, which were designed to fit the features of artificial light sources 1,22,25 . To date, there is no report focusing on device engineering itself using well‐developed materials such as N719 sensitizer, I − /I 3 − redox couple, and platinum counter electrode (CE) under the consideration of dim light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…After thorough investigations, there is a general agreement on the structural requirements of porphyrins to be used in DSSCs: 1) at least one anchoring group must be present for the covalent binding to the semiconductor surface [9], 2) metallic complexes (MP), especially the zinc ones, are preferred to free-base (H 2 P), because of their longer-lived singlet excited states and much lower oxidation potentials [10], and 3) bulky electron-donor meso-substituents favor electron injection in the semiconductor, as they originate an intrinsic dipole moment [11]. High efficiencies have been achieved for TiO 2 -based devices sensitized, for example, with free-base [12] and zinc porphyrin derivatives [13], presenting one or more carboxylic acid appends as anchoring groups, either in β [9,14] or meso [15,16] positions of the porphyrin central core, and also with multiple donor groups at the meso positions [17,18,19]. The combination of the donor groups, and the electron-withdrawing carboxy group, contributes to create the push–pull effect, channelling the photoexcited electrons toward TiO 2 and improving charge separation.…”
Section: Introductionmentioning
confidence: 99%